Foreign Investors and Stock Price Crash Risk: Evidence from Vietnam. (21st December 2018) - Vo, Xuan Vinh
Abstract: Examining stock price crash risk in emerging economies is important since emerging equity markets are characterized by excessive volatility and weak corporate governance. This paper investigates the association between foreign ownership and crash risk using a data sample of firms listed on the Ho Chi Minh City Stock Exchange over the period 2007–2015. Employing a number of econometric techniques for panel data analysis, the paper shows that foreign investors are positively associated with future stock price crash risk. Importantly, this finding highlights the critical problem of information asymmetry in emerging markets. This paper has strong implications for portfolio investment and risk management. The paper is also relevant for financial market supervisory body in maintaining safe and sound financial markets.